Pores size distribution and pores volume density of mollisols and vertisols under different cropping intensity managements with no - tillage - Behrends Kraemer, Filipe; Castiglioni, Mario Guillermo; Morras, Héctor José María; Fernández, Patricia; Alvarez, Carina (Elsevier, 2021)
In the Argentina Pampas, one of the most extensive agricultural areas in the temperate fringe of southern hemisphere, soil health is jeopardized mostly by the decline of physical and biological properties due to soil fragility and agricultural managements, even under No-tillage (NT). In this study, topsoil physical health of three Mollisols and one Vertisol under two agricultural managements with no-tillage (good and poor agricultural practices -GAP and PAP-, differing mostly in their cropping intensity -CI-) was evaluated by the indirect measurement of porosity features. Two types of pore features derived from soil water release curves (SWRC) of undisturbed samples at three depths (0.0–0.05, 0.05–0.010 and 0.010–0.20 m) were employed: a) pores size distribution (>1000, 300, 50 and < 50 µm) and b) pore volume density parameters: location (Dmode, Dmean and Dmedian) and shape (SD, Skewness and Kurtosis). Pore parameters were related to management variables, to clay mineralogy and to several soil physical and chemical properties allowing to i) evaluate the effects of cropping intensification on soil physical properties; ii) evaluate the effects of intrinsic and dynamics factors on the behaviour of pore variable; iii) build an optimal pore size frequency curve to assess soil health. Among all porosity features assessed, PMac>300 µm and Dmode showed close relationships with agricultural management variables and were positively related to a labile organic carbon fraction (POCc) and to the aggregates stability tests, regardless of the soil type. Thus, they both may be selected as sound indicators of physical health status of different pampean soils under NT cultivation. Particularly, in the PAP treatments and for the three depths evaluated, PMac>300 µm showed values below critical thresholds, highlighting the physical deterioration of soils subjected to this management. Cropping intensification expressed by the CI index was also strongly related with large pores and soil properties (i.e. organic carbon and aggregates stability). These results demonstrate that cropping intensification expressed by the CI index was effective to counteract compaction processes in a variety of soils of the Pampa region and must be seen as an important strategy to avoid porosity loss and to improve the benefits of NT.